The meaning of the poem "Manicomio" by Alberto Mostajo from the perspective of the analysis of poetic discourse - Choquepata, Tania (2019)
The objective was to analyze and interpret the meaning of the poem "Manicomio" by Alberto Mostajo from the perspective of the analysis of poetic discourse. The research method applied was hermeneutics and the technique was discourse analysis, by which the following dimensions were considered: textual, semiotic, enunciative and pragmatic. The Asylum poem is a linguistic construction that meets the criteria of textuality. At a semiotic level, the poem gives us to understand the world as an Asylum for nostalgia, the deep sadness that the author feels when he sees the blindness and the unconsciousness of people facing the problems of society. At the enunciative level, Mostajo expresses in the first person through the lyrical subject who observes how society is indifferent to the events or events that surround them, and focus on the pleasures of life. At the pragmatic level, the lyrical subject fulfills transmitting ideas to the reader or listener with the intention of generating reflection and awareness.